2002
DOI: 10.1093/milmed/167.2.132
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Navy and Marine Corps Hearing Conservation Program, 1995–1999: Mean Hearing Thresholds for Enlisted Personnel by Gender and Age Groups

Abstract: This study presents mean hearing thresholds from a cross-sectional study of 68,632 monitoring audiograms submitted to the Navy Environmental Health Center for 1995 to 1999. Records included U.S. Navy and U.S. Marine Corps enlisted personnel (Navy men = 51,643; Navy women = 4,184; Marine Corps men = 12,251: Marine Corps women = 554). Mean hearing thresholds were calculated for age groups (17-24, 25-29, 30-34, 35-39, 40-44, 45-49, and 50 years and older), gender (male/female), and service (Navy/Marine Corps). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We found an association between reduced hearing and work on board navy vessels. In a study comparing hearing thresholds in U.S. Navy and Marine Corps with OSHA age-corrected values of hearing thresholds (Bohnker et al 2002a ), it was concluded that men in Navy and Marine Corps had higher threshold levels than according to OSHA. Another study reported that working on board surface warships was more damaging to hearing than work at shore duty stations (Trost and Shaw 2007 ), and an increased risk of hearing impairment was indicated in a study among flight deck personnel and engine room workers on an aircraft carrier compared with administrative personnel (Rovig et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found an association between reduced hearing and work on board navy vessels. In a study comparing hearing thresholds in U.S. Navy and Marine Corps with OSHA age-corrected values of hearing thresholds (Bohnker et al 2002a ), it was concluded that men in Navy and Marine Corps had higher threshold levels than according to OSHA. Another study reported that working on board surface warships was more damaging to hearing than work at shore duty stations (Trost and Shaw 2007 ), and an increased risk of hearing impairment was indicated in a study among flight deck personnel and engine room workers on an aircraft carrier compared with administrative personnel (Rovig et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 16% of disabling hearing loss in adults worldwide is due to occupational noise (Nelson et al, 2005). The military is one of the world's most noise hazardous occupations, and NIHL in the military continues to be an acute and costly problem despite hearing conservation programs emphasizing personal hearing protection devices (HPDs) (Bohnker et al, 2002;Wolgemuth et al, 1995). Hearing damage from acoustic trauma accounts for up to 47% of all wounded in action evacuations from Operation Iraqi Freedom and Operation Enduring Freedom and is the fourth leading reason for medical referral for combatants returning from deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in line with previous research on the US Navy and US Marine Corps personnel indicating that mean threshold levels for men were worse than the OSHA age-adjusted values. [ 6 16 ] Deteriorated hearing thresholds were also discovered for officers serving in an infantry regiment of the Swedish Army. [ 27 ] Here, significant hearing loss was found for all frequencies investigated when compared to ISO 1999(1990), database A.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 3 ] In the military, noise exposure is among the most prevalent occupational health hazards, with hearing loss commonly reported. [ 3 4 5 6 ]…”
Section: Introductionmentioning
confidence: 99%